The impact of financial market development on economic growth in Saudi Arabia during the period 1990-2023 - Mounira, Debbi; Bouaita, Abderrezzak; Kalkoul, Abderrezzak (The International tax journal, 2025)
This study aims to measure the impact of stock market development on economic growth in Saudi Arabia during the period 1990-2023. Stock market development is represented by three indicators: market capitalization rate, trading volume rate, and market performance index, while economic growth is expressed through GDP per capita. Using the Autoregressive Distributed Lag (ARDL) model, the study found a significant positive impact of market capitalization rate and market liquidity (measured by trading volume rate) on economic growth in both the short and long run. Conversely, the market performance index showed a negative impact on economic growth in both the short and long run. The results indicate that market size and liquidity have contributed to financing real economic activity and economic growth in Saudi Arabia. Therefore, policymakers and stakeholders in the Saudi financial market should improve capital market operations and implement favorable regulations to enhance market efficiency and effectiveness.